Preferential sky window: proposal of a new parameter to control urban daylight access - Leder, Solange Maria (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
Indoor daylighting is strongly influenced by sky obstruction by the urban environment. Considering this premise, urban legislation may set limits of land use to provide and to protect the right to daylight and solar access. This study proposes a daylight accessibility control parameter for the urban environment. The characterization of this parameter takes into account three aspects: i) relative lighting contribution of several sky vault patches, ii) light incidence angle cosine effect, and iii) the indoor sky vault visibility percentage. The integration of these aspects allowed the characterization of the effective lighting potential of the sky indoors, and the definition of a sky area, called Preferential Sky Window. Daylight performance of the Preferential Sky Window in an indoor environment was analyzed. Results showed strong correlation between the proposed parameter and indoor daylighting performance. Daylight performance was simulated by a computational method. The proposed could be extensively used in building regulations to safeguard daylight availability.